Estudios (inter)culturales en clave de-colonial - Walsh McDonald, Catherine Elizabeth (2010)
“Cultural studies” in Latin America make part of a naming policy manifested on legacies and frequently mapped as a whole, hiding or overlooking differences within themselves. This paper looks at the source of cultural studies in Latin America in general, and at the Quito Simón Bolívar Andean University in particular; as well as which policies are followed, which project(s) and which knowledge foundations and perspectives. It considers aspects involved in conceiving and building cultural studies as a political-intellectual project, inter-cultural, inter-epistemic decolonially-based and related challenges and hindrances, including them in the problematic of “uni”-versity itself.